(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: This study aimed to establish a standardized and locally applicable protocol for collecting and morphologically identifying house dust mites from household dust in Ho Chi Minh city. Method: Household dust samples were collected from mattresses, sofas, and carpets in 100 residential units across Ho Chi Minh city using a handheld vacuum device. The collected samples were subjected to a series of physical and chemical processing steps, including ethanol treatment and saturated saline flotation, to isolate mites. Morphological identification was performed using light microscopy, following a modified protocol optimized to preserve diagnostic structures. Results: The refined protocol demonstrated high efficacy, yielding 65.6% of house dust mites specimens with intact morphological features adequate for taxonomic identification. House dust mites were detected in 90% of surveyed households, indicating widespread environmental presence. Conclusion: The established protocol is technically feasible and effective for field implementation in urban Vietnamese settings. It provides essential baseline data for future ecological surveys and supports the development of region-specific allergen sources, thereby enhancing the diagnostic relevance of allergy testing in Vietnam